Profil Kemampuan Spasial Siswa Koleris - Monalisa, Lioni Anka; Susanto, Susanto; Hussen, Saddam; Hibatullah, Ifka Nurafni (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2024)
Students with different personality types have different levels of visual-spatial intelligence. One of them is a koleris student who has level 1 in the category of imagination and conceptualization. Visual-spatial intelligence is a part of spatial ability that is related to the ability of the brain. In this study, it will be described regarding the spatial abilities of koleris students which include the ability of spatial perception, spatial visualization, and mental rotation. The research subjects were students of class X MIPA 1 of SMAN 1 Jember who were classified as personality types based on the results of the questionnaire. Next, two students from the koleris type were given the spatial ability test questions and were interviewed to test the credibility of the students' answers. The results of the analysis of answers to the test questions and interviews will be described in full and then drawn conclusions. The results showed that the spatial ability profile of koleris students was able to fulfill all indicators of spatial perception, two indicators of spatial visualization, and two indicators of mental rotation. A good organizational system makes students koleris able to draw three-dimensional shapes well and correctly